Upaya Kantor Depan Dalam Meminimalisir Keluhan Tamu Di Hotel Cavinton Yogyakarta - Rosy Maelany Kisti; Citra Unik Mayasari (STIE Pariwisata API Yogyakarta, 2019)
Cavinton Hotel Yogyakarta is one of the four star hotels that has location in the center of Yogyakarta, so Cavinton Hotel Yogyakarta become crowded during long holidays such as Eid holidays, school holidays, christmas and new year holidays.When the hotel was crowded there was any problems which caused inconvenience to guests, that make the guest have a complaints when staying at hotel. Data collection methods in the preparation of the research is a method of observation, interviews, documentation study and analysis methods library study of qualitative analysis method of data analysis without the use of statistical analysis. Complaints submitted by guests are directly by conveying direclty to staff hotel and indirectly by writig a comment on the online travel agent review. Complaints submitted by guest are about facilities complaint, staff/ attitudinal complaint, service releated problem and unusual complaint. If the complaint is not immediately handled, the impact that occurs is the guest becomes angry and dissapointed, guest do not return to the hotel for stay, then the hotel became a little interested, this causes hotel revenues is down. Front office efforts to handling guest complaints during the high season periods are adding personnel, re-checking guests room bookings, make sure the room that guests use are ready to use.